Use of the Daily Phone Diary to Study Religiosity and Mood: Convergent Validity. Issue 2 (3rd April 2017) - Szczesniak, Rhonda D.; Zou, Yuanshu; Dimitriou, Sophia M.; Quittner, Alexandra L.; Grossoehme, Daniel H.
Abstract : Studies of religious/spiritual behavior frequently rely on self-reported questionnaire data, which is susceptible to bias. The Daily Phone Diary (DPD) was developed to minimize bias in reporting activities and behavior across a 24-hour period. A cross-sectional study of 126 parents of children with cystic fibrosis was used to establish the validity of the DPD to study religious/spiritual behaviors. Longitudinal models were used to determine the odds of improved mood during religious/spiritual activities. Convergent validity was found. Participants had increased odds of improved mood during religious/spiritual activities compared to nonreligious/spiritual activities. Associations with gender and religious affiliations were found. The DPD is a valid tool for studying religious/spiritual activities and opens novel avenues for chaplaincy research and the development of chaplaincy interventions incorporating these findings.